2015
DOI: 10.1039/c5mb00292c
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict the intracellular metabolic state of a cell based on extracellular metabolite data?

Abstract: The analysis of extracellular metabolites presents many technical advantages over the analysis of intracellular compounds, which made this approach very popular in recent years as a high-throughput tool to assess the metabolic state of microbial cells. However, very little effort has been made to determine the actual relationship between intracellular and extracellular metabolite levels. The secretion of intracellular metabolites has been traditionally interpreted as a consequence of an intracellular metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…Results indicated that the intracellular and extracellular levels of aspartate, 2‐oxoglutarate, benzoate and decanoate changed in opposite directions, while a total of six metabolites were uniquely detected in the spent culture media (Granucci et al . ).…”
Section: Intracellular Metabolites Extracellular Metabolites and Thementioning
confidence: 97%
See 4 more Smart Citations
“…Results indicated that the intracellular and extracellular levels of aspartate, 2‐oxoglutarate, benzoate and decanoate changed in opposite directions, while a total of six metabolites were uniquely detected in the spent culture media (Granucci et al . ).…”
Section: Intracellular Metabolites Extracellular Metabolites and Thementioning
confidence: 97%
“…; Granucci et al . ). The supernatant obtained is then used for the metabolomics analysis (Pinu et al .…”
Section: Intracellular Metabolites Extracellular Metabolites and Thementioning
confidence: 97%
See 3 more Smart Citations